Human factors challenge in entrepreneurship development : an explorative study in a developing economy context / Jocelyn Sackey, Mohammed-Aminu Sanda and Ylva Fältholm - Sanda, Mohammed-Aminu; Fältholm, Ylva; Sackey, Jocelyn (Faculty of Business Management, 2013)
This study explored the barriers to entrepreneurial development in Ghana with the aim of building a knowledge base for successful entrepreneurship development initiatives in a developing economy context. An exploratory approach was used with both retrospective and qualitative data collected through a survey. The results showed that the functionalities of the numerous schemes initiated to support individual entrepreneurs‟ growth were constrained due to the inherent constraints in the design of the guiding frameworks for such schemes. The study also showed that the several policies and structures initiated differently by various governments since Ghana‟s independence in March 1959 could not help enhance entrepreneurial development, because the entrepreneurial environment created for entrepreneurship development was not very friendly to the individual entrepreneurs, By implication, the study provides learning on the need to bridge the distance that exist between the designers/implementers of entrepreneurship development policies/frameworks and the individual entrepreneurs (humans).